Cardiac Causes of Chest Pain in Children - Ye.V. Pshenichnaya; Ye.V. Bordyugova; N.N. Konopko; А.V. Dubovaya; S.A. Parshin; А.P. Koval; Ye.S. Uzun (Zaslavsky O.Yu., 2014)
This article presents the features of blood supply and innervation of the myocardium, causing occurrence of pain. The characteristics, duration, irradiation, conditions of onset and regression of anginal, associated with myocardial ischemia, and non-anginal pain are provided. Authors had described clinical characteristics, aspects of the differential diagnosis of heartache in children with congenital heart disease, anomalies of coronary artery junction, myocardial infarction, carditis, pericarditis, primary cardiomyopathy, heart rhythm disorders.